Mapping of aetiologies and clinical presentation of acute colitis: Results from a prospective cohort study in a tertiary centre. (28th May 2021) - Meyer, J; Schrenzel, J; Balaphas, A; Delaune, V; Abbas, M; Morel, P; Puppa, G; Rubbia-Brandt, L; Bichard, P; Frossard, J -L; Toso, C; Buchs, N; et al.
Abstract: Objective: Our objective was to describe the aetiologies of acute colitis and to identify patients who require diagnostic endoscopy. Methods: Patients with symptoms of gastrointestinal infection and colonic inflammation on computed tomography were prospectively included. Those immunosuppressed, with history of colorectal cancer or inflammatory bowel disease (IBD) were excluded. Stools were screened with BD-Max and BioFire FilmArray GI panel. Faecal calprotectin was determined. Patients with negative BD-Max underwent colonoscopy. The study was registered into clinicaltrials.gov (NCT02709213). Results: One hundred and seventy-nine patients were included. BD-Max was positive in 93 patients (52%) and FilmArray in 108 patients (60.3%). Patients with infectious colitis (n = 103, 57.5%) were positive for Campylobacter spp (n = 57, 55.3%), Escherichia coli spp (n = 8, 7.8%), Clostridium difficile (n = 23, 22.3%), Salmonella spp (n = 9, 8.7%), viruses (n = 7, 6.8%), Shigella spp (n = 6, 5.8%), Entamoeba histolytica (n = 2, 1.9%) and others (n = 4, 3.9%). Eighty-six patients underwent colonoscopy, which was compatible with ischemic colitis in 18 patients (10.1%) and IBD in 4 patients (2.2%). Among patients with negative FilmArray, a faecal calprotectin >625μg/g allowed identifying patients with IBD with an area under ROC curve of 85.1%. Introduction of a diagnostic management algorithm including FilmArray and faecal calprotectin could allow decreasing unnecessary colonoscopies from 82 to 29 (corresponding to a decrease of 64.6%). Conclusion: Computed tomography-proven colitis was mostly of infectious aetiology. Diagnostic management of patients with acute colitis should include broad molecular testing of the stools and, in patients with a calprotectin concentration >625μg/g, colonoscopy to exclude IBD.